Optimal Placement and Sizing of Distributed Generators Based on a Novel MPSI Index - Ruhaizad, Ishak; Azah, Mohamed; Abdalla, Ahmed N.; Mohd Zamri, Che Wanik (Elsevier, 2014)
The Objective: This paper presents a method to identify the optimal location and size of DGs based on the power stability index and particle swarm optimization (PSO) algorithm.Materials and methods: First, a novel maximum power stability index (MPSI) is derived from the well-established theorem of maximum power transfer. The MPSI is utilized as an objective function to determine the optimal DG locations. Next, a PSO-based model with randomized load is developed to optimize DG sizing in view of the system’s real power losses.Results and Conclusion: Lastly, a IEEE 30-bus test system is employed in the simulation. The performance of proposed MPSI index are comparable with other voltage stability indices. The DG optimization model considering voltage stability and loss minimization provides better results compared to that obtained using only loss minimization approach.